Pentingnya Pendidikan Entrepreneurship Sebagai Upaya Pembentukan Karakter Entrepreneur Mahasiswa Pencetak Lapangan Kerja - Moch. Dicky Riza (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Systematically, this paper describes the reasons for the importance of educational entrepreneurship in character building for students and assumes that educational entrepreneurship will encourage students to start entrepreneurship. The many problems of poverty do have consequences on competition in getting jobs because in Indonesia it is very limited. It is only fitting that as the next generation of the nation in the future, students should be persistent in encouraging the spirit of entrepreneurship so that they do not rely on limited job opportunities but must become job providers and creators. The method used in this study is the Literature Review method, which is to review the themes raised. The way to collect information from this library activity is from various library sources which are needed as a source for developing new ideas in the form of a framework which will eventually become a theory. Entrepreneurial character through learning about entrepreneurship can be built through higher education. For students to cultivate entrepreneurial traits, they must start early because truly reliable and successful entrepreneurs start from small to large things or businesses, not the other way around. Students must get rid of thoughts about entrepreneurship, namely when starting a business they must have large capital money and feel unable to take risks that will be faced in the future.